Thermal Energy Consumption in the Heat-Technology Production of Solid Composite Fuel From Low-Grade Raw Materials; European Physical Journal Web of Conferences (EPJ Web of Conferences); Vol. 110 : Thermophysical Basis of Energy Technologies - Tabakaev R. B. Roman Borisovich (2016, 2016)
Title screen